Effectiveness of mobile stroke units in reducing time to thrombolysis in acute ischemic stroke: a scoping review - Nicholas Aderinto; Gbolahan Olatunji; Emmanuel Kokori (International Journal of Emergency Medicine)
Abstract Background Timely thrombolysis within the golden hour (≤ 60 min from onset) is critical for minimizing disability in acute ischemic stroke (AIS). Mobile stroke units (MSUs) enable prehospital thrombolysis, with effectiveness varying by urban versus rural settings, the presence of an onboard neurologist, and telemedicine models. This study maps evidence on MSU effectiveness in reducing time to thrombolysis in AIS compared to standard emergency medical services (EMS), examines factors modulating effectiveness (e.g., geographic setting, operational protocols), and identifies research gaps. Methods This scoping review followed the Arksey and O’Malley framework and PRISMA-ScR guidelines. PubMed, Embase, Google Scholar, Scopus, and Cochrane Library were searched from January 2008 to March 2025 for peer-reviewed studies reporting thrombolysis timing in AIS with MSUs. Included randomized controlled trials (RCTs), observational studies, and meta-analyses (using both fixed-effects and random-effects models) were synthesized narratively, with data on time reductions, treatment rates, outcomes, and limitations extracted by two blinded reviewers (NA and EK) and tabulated. Results Thirteen studies (five RCTs, six observational studies, and two meta-analyses) involving 39,800 patients across urban and mixed settings were included. MSUs reduced the median onset-to-needle time by 20–41 min, increasing golden-hour rates from less than 5% (EMS) to 21–33%. Urban settings reduced time by 25–41 min and onboard neurologists by up to 41 min, compared to 20–40 min in rural areas and 30–37 min with telemedicine. Thrombolysis rates increased by 10–20% with MSUs compared to EMS, with earlier treatment associated with improved 90-day mRS outcomes of 0–1. Gaps include limited rural data, sparse real-world evidence of cost-effectiveness, and inconsistent reporting of outcomes. Conclusion MSUs enhance access to thrombolysis in AIS, resulting in substantial time savings and potential benefits to outcomes, particularly in urban settings. Further research is needed on rural applicability, cost-effectiveness, and standardized outcomes to optimize global MSU implementation.